Understanding zeros and splittings of ordered tree amplitudes via Feynman diagrams - Kang Zhou (Journal of High Energy Physics)
Abstract In this paper, we propose new understandings for recently discovered hidden zeros and novel splittings of scattering amplitudes, by utilizing Feynman diagrams. The study focus on ordered tree level amplitudes of three theories, which are Tr(ϕ 3), Yang-Mills, and non-linear sigma model. We find three universal ways of cutting Feynman diagrams, which are valid for any diagram contributing to the amplitude, allowing us to separate the full amplitude into two/three pieces. We show that the first type of cuttings corresponds to hidden zeros, the second one gives rise to 2-splits, while the third one leads to 3-splits called smooth splittings. Throughout this work, we frequently use the helpful auxiliary technic of thinking the resulting pieces as in orthogonal spaces. However, final results are independent of this auxiliary picture.